Portfolio Resilience: Insights from S&P ESG and BSE Indices During Pandemics - Preeti Bai Agrawal; Dr. Anuradha Samal (Utilitas Mathematica, 2025)
Purpose: Portfolio management is a complex blend of strategy and analysis that serves as the cornerstone of investment decision-making aiming to optimize returns while mitigating risk. In this exploration, we scrutinize the association between sustainable portfolios, integrating environmental, social, and governance (ESG) factors and normal portfolios which predominantly prioritize financial metrics. This study examines the performance of the S&P BSE 100 index, the S&P ESG BSE 100 index, and a portfolio of both indices during different pandemic phases. The study also compares these portfolios against the benchmark S&P BSE Sensex index. The performance of the indices is evaluated, understand the risk composition and finding out the possible outcomes in different market scenarios. Methodology: The data is divided into four periods: pre-pandemic (2017-2018), pandemic (2019-2020), mild pandemic (2021-2022), and post-pandemic (2023-2024). The study assesses annualized returns, risk measures as well as used risk adjusted ratios such as Sharpe ratio, Treynor ratio, Jensen's alpha and VaR across different market conditions. Moreover, systematic and unsystematic risks are examined to understand the risk composition of the portfolios. The methodology also incorporates Monte Carlo simulation with 10,000 iterations to simulate potential portfolio outcomes is used. Findings: The findings of the study are as follows: • The S&P ESG BSE 100 index outperformed the S&P BSE 100 index during the pre-pandemic and mild pandemic periods, but underperformed during the pandemic and post-pandemic periods. • Portfolios containing both indices generally outperformed the S&P BSE Sensex index the pandemic period. • The VaR analysis shows that the risk of all indices and portfolios decreased from the pre-pandemic period to the post-pandemic period. • The Monte Carlo Simulation indicates average monthly returns of 0.01% to 0.09% with associated volatility (standard deviation) ranging from 0.79% to 1.56%. At a 5% confidence level, potential losses are not expected to exceed -0.0129 to -0.0102. Conclusion: The study suggests that Sustainable investing can be a viable strategy for Indian investors, but it is important to consider the potential risks and returns during different economic periods. The findings also highlight the importance of diversification, as portfolios containing both the S&P BSE 100 index and the S&P ESG BSE 100 index generally outperformed the benchmark S&P BSE Sensex index.